Analisis Efisiensi Kerja Dalam Memediasi Pengaruh Artificial Intelligence Dan Kepemimpinan Terhadap Kinerja Sumber Daya Manusia - Enrico Wongsotanoto; Ike Rachmawati; Yunus Handoko (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) and leadership on work efficiency and human resource (HR) performance at PT Tabira Petro Energi. The research method employed is a quantitative approach using a survey conducted on the entire population of 52 employees through a census technique. Data were collected via questionnaires and anssalyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that AI and leadership have a positive and significant impact on work efficiency and HR performance. Furthermore, work efficiency is proven to positively affect HR performance and serves as an intervening variable mediating the influence of AI and leadership on HR performance. These findings suggest that proper AI implementation and supportive leadership can enhance efficiency to optimize No Halaman Jurnal Ekonomi Manajemen dan Bisnis, Volume X, Nomor X, Bulan Tahun:hal pertama-hal terakhir HR performance in the digital transformation era. This research provides practical contributions for companies in designing technology-based HR management strategies.